OHMIC DISTORTION OF CURRENT-POTENTIAL CURVES AT WALL-JET ELECTRODES - Coles, B; Compton, R; Brett, C; Brett, A (1995)
The ohmic distortion of current-voltage curves for the wall-jet hydrodynamic electrode is investigated using a finite-element approach with the circuit analysis program spice. Simulated and experimental data are presented, showing the displacement of the half-wave potential and the potential-dependent error in the Tafel slope. Error curves are given as a guide to the maximum current levels which may be used in practice with different electrolyte concentrations. © 1995.